Modernization of agriculture and long-term growth - Dennis Tao Yang; Xiaodong Zhu (Institute for the Study of Labor (IZA), 2010)
This paper develops a two-sector model that illuminates the role played by agricultural modernization in the transition from stagnation to growth. When agriculture relies on traditional technology, industrial development reduces the relative price of industrial products, but has a limited effect on per capita income because most labor has to remain in farming. Growth is not sustainable until this relative price drops below a certain threshold, thus inducing farmers to adopt modern technology that employs industry-supplied inputs. Once agricultural modernization begins, per capita income emerges from stasis and accelerates toward modern growth. Our calibrated model is largely consistent with the set of historical data we have compiled on the English economy, accounting well for the growth experience of England encompassing the Industrial Revolution.
Keywords: O41; O33; N13; 330; long-term growth; transition mechanisms; relative price; agricultural modernization; structural transformation; Industrial Revolution; England